2013
DOI: 10.1002/bio.2461
|View full text |Cite
|
Sign up to set email alerts
|

Development of a rapid and high‐performance chemiluminescence immunoassay based on magnetic particles for protein S100B in human serum

Abstract: Protein S100B is a clinically useful non-invasive biomarker for brain cell damage. A rapid chemiluminescence immunoassay (CLIA) for S100B in human serum has been developed. Fluorescein isothiocyanate (FITC) and N-(aminobutyl)-N-(ethylisoluminol) (ABEI) are used to label two different monoclonal antibodies of anti-S100B. Protein S100B in serum combines with labeled antibodies and can form a sandwiched immunoreaction. A simplified separation procedure based on the use of magnetic particles (MPs) that were coated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The detection limit, coefficient of variation, and recovery rates indicated that our novel method exhibited high reproducibility with low deviation, and the recovery experiment confirmed the accuracy of this assay system. [27][28][29] These results indicated the stability of our detection system. We also provide a quantitative comparison of the novel approach and Elecsys® for measuring the serum concentration of S100B (216 samples).…”
Section: Discussionmentioning
confidence: 65%
“…The detection limit, coefficient of variation, and recovery rates indicated that our novel method exhibited high reproducibility with low deviation, and the recovery experiment confirmed the accuracy of this assay system. [27][28][29] These results indicated the stability of our detection system. We also provide a quantitative comparison of the novel approach and Elecsys® for measuring the serum concentration of S100B (216 samples).…”
Section: Discussionmentioning
confidence: 65%
“…One possibility is to use magnetic nano-/micro-particles labeled with an antibody, so each analytical step is conducted without washing. Finally, the generated immunocomplex for a given analyte is removed from the solution, using a magnet, to be deposited in the measuring area for CL (Qin et al, 2012;Fu et al, 2012;Zhang et al, 2013) or ECL detection Gan et al, 2013;Zhou et al, 2013;Zhu et al, 2012;Liao et al, 2014). Gan et al (2013) described an ECL immunoassay for carbohydrate antigen 19-9 (CA 19-9) in serum.…”
Section: Static Systems (Single Spot Tube Dot Array)mentioning
confidence: 99%
“…S100B is released by cell death and once in circulation it has a short halflife (30 min) [176]. Serum S100B quantification is usually performed by immunoassay-based techniques sometimes adapted to automated test platforms [177,178]. Most of these methods employ sandwich-type immunoassay configuration with two different antibodies directed to the beta subunit.…”
Section: S100bmentioning
confidence: 99%